Renewing the house Trajectories of social life in the yucayeque (community) of El Cabo, Higüey, Dominican Republic, AD 800 to 1504 - Samson, Alice V.M (Sidestone Press, 2010)
This study is a contribution to the household archaeology of the Caribbean. The aim of the research was to come to a material definition of the precolonial house, rather than rely on the few, short, Spanish colonial descriptions. Archaeological research from the indigenous Taíno site of El Cabo in the Dominican Republic is presented and seven centuries of community history from development and growth, to eventual demise after European contact is narrated through the dominant structure, the house. The interpretation of over 2000 domestic features, associated artefact assemblages and the spatial organization of the settlement between ca. AD 800 and 1504 is described in detail. No archaeological house plans have previously been published for precolonial Hispaniola. The data from El Cabo tips the scales the other way, contributing to a history of indigenous life through the study of the native house and its diachronic materialization - the House Trajectory.